Ulnar nerve involvement at the wrist in idiopathic mild to moderate carpal tunnel syndrome: electrophysiological and ultrasonographic study - Walaa Elwakil; Hussein Elmoghazy Sultan; Marwa Hassan; Mohamed Elshafei; Esraa Hammad (Egyptian Rheumatology and Rehabilitation, 2024)
Abstract Background Carpal tunnel syndrome (CTS) is a common entrapment neuropathy. It is clinically presented by nocturnal pain, paresthesia, and weakness in the distribution of the median nerve. However, extra-median symptoms may develop in some patients, particularly those with mild to moderate CTS. This raised the assumption of possible concomitant ulnar nerve entrapment at the wrist, or Guyon's canal syndrome (GCS). The aim of this study is to evaluate functional and structural changes that may take place in the ulnar nerve at the wrist in those patients. Methods This is a retrospective case–control study that included forty patients with mild to moderate CTS and 40 matched subjects as a control group. Electrophysiological evaluation was done for all the participants in addition to measuring median and ulnar nerves sonographic parameters in the form of median cross-sectional area (m-CSA) at the level of pisiform bone, median flattening ratio (m-FR), median swelling ratio (m-SR), the difference between m-CSA at the inlet of the carpal tunnel and m-CSA at the distal third of the pronator quadratus (Δ m-CSA), as well as the ulnar cross-sectional area (u-CSA) at the same level. Results The u-CSA was larger in the patients relative to the control (5.23 ± 1.21 mm2 versus 3.28 ± 0.64 mm2). It did not correlate with m-CSA. However, a statistically significant correlation was demonstrated between u-CSA and median motor conduction parameters (P ≤ 0.001). Conclusion Although patients with mild to moderate idiopathic CTS may have normal electrophysiological parameters of the ulnar nerve, ultrasonographic evaluation is valuable to detect early ulnar nerve structural changes, which appear to be likely due to concomitant distal ulnar nerve entrapment at the Guyon’s canal, which may contribute to the development of extra-median symptoms in those patients.